Clinical Cases in LAA Occlusion : Indication, Techniques, Devices, Implantation - Bergmann, Martin W.; Tzikas, Apostolos; Wunderlich, Nina C. (Springer International Publishing : Imprint: Springer, 2017)
This concise practical guide is designed to facilitate the clinical decision-making process in the management of LAA occlusion procedures by reviewing a number of cases and defining the various diagnostic and management decisions open to clinicians. Clinical Cases in LAA Occlusion is well illustrated but concise, enabling the reader to obtain relevant information regarding both standard and unusual cases in a rapid, easy to digest format. Each case includes a narrative description and patient management tips.
Keywords: Medicine.; Interventional radiology.; Cardiology.; Cardiac surgery.; elektronické knihy; electronic books